Cross-scale Adaptation Challenges in the Coastal Fisheries: Findings from Lebesby, Northern Norway - West, Jennifer J.; Hovelsrud, Grete K. (ARCTIC, 2010)
Cross-scale adaptation challenges in the coastal fisheries in Lebesby municipality, Finnmark County, northern Norway are examined on the basis of fieldwork conducted there. Although fishery actors in Lebesby are aware of, experience, and describe a number of connections between climate variability and coastal fishing activities, they do not characterize their livelihoods as being particularly vulnerable to climate change. Nevertheless, they identify a range of social factors that shape the flexibility of coastal fishing activities and livelihoods to deal with changing environmental conditions. We argue that these factors, and actors' perceptions of their own resilience, constitute important aspects of adaptive capacity and may challenge local responses to climate variability and change. We identified four adaptation arenas: local perceptions of vulnerability and resilience to climate change, Lebesby's social and economic viability, national fishery management and regulations, and the markets and economy of coastal fishing. The adaptation arenas arise and interact across geographic and temporal scales, creating specific barriers and opportunities for local adaptation. Our findings suggest the need to pay close attention to the cross-scale adaptation challenges facing Arctic communities that depend on natural resources. The concept of adaptation arenas helps to illustrate these challenges and should be applied more widely. Les défis d'adaptation à plusieurs échelles dans le secteur des pêches côtières de la municipalité de Lebesby dans le comté de Finnmark, nord de la Norvège, sont examinés en fonction des études sur le terrain qui y ont été réalisées. Bien que les parties prenantes du secteur des pêches de Lebesby soient conscientes de l'existence d'un certain nombre de liens entre la variabilité du climat et les activités de pêche côtière, elles n'affirment pas que leur gagne-pain est particulièrement vulnérable au changement climatique. Elles dénotent néanmoins une série de facteurs sociaux qui exercent une ...